Climate change research and action must look beyond 2100. (24th September 2021) - Lyon, Christopher; Saupe, Erin E.; Smith, Christopher J.; Hill, Daniel J.; Beckerman, Andrew P.; Stringer, Lindsay C.; Marchant, Robert; McKay, James; Burke, Ariane; O'Higgins, Paul; Dunhill, Alexander M.; Allen, Bethany J.; et al.
Abstract: Anthropogenic activity is changing Earth's climate and ecosystems in ways that are potentially dangerous and disruptive to humans. Greenhouse gas concentrations in the atmosphere continue to rise, ensuring that these changes will be felt for centuries beyond 2100, the current benchmark for projection. Estimating the effects of past, current, and potential future emissions to only 2100 is therefore short‐sighted. Critical problems for food production and climate‐forced human migration are projected to arise well before 2100, raising questions regarding the habitability of some regions of the Earth after the turn of the century. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation. As a result, we argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100. Abstract : We argue that projections of climate and its effects on human well‐being and associated governance and policy must be framed beyond 2100. To highlight the need for more distant horizon scanning, we model climate change to 2500 under a suite of emission scenarios and quantify associated projections of crop viability and heat stress. Together, our projections show global climate impacts increase significantly after 2100 without rapid mitigation.